1989
DOI: 10.1002/chin.198950008
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: The Structures of Lanthanum Hydroxide Nitrates Investigated by the Rietveld Profile Refinement Technique.

Abstract: La(OH)2NO3 crystallizes in space group P21/m with Z=2 and La(OH)2NO3·H2O crystallizes in C2/m with Z=4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…Similar X-ray powder study on structural changes of La(OH) 2 (NO 3 )‚H 2 O due to dehydration has been reported earlier. 53 Photoluminescence Study. The luminescence spectra of Pr-(III) compounds are more complex in comparison to that of other lanthanide(III) systems such as Eu 3+ , as Pr(III) can show emission lines originating from three different levels ( 3 P 0 , 1 D 2 and 1 G 4 ) which span the visible and NIR regions.…”
Section: Resultsmentioning
confidence: 99%
“…Similar X-ray powder study on structural changes of La(OH) 2 (NO 3 )‚H 2 O due to dehydration has been reported earlier. 53 Photoluminescence Study. The luminescence spectra of Pr-(III) compounds are more complex in comparison to that of other lanthanide(III) systems such as Eu 3+ , as Pr(III) can show emission lines originating from three different levels ( 3 P 0 , 1 D 2 and 1 G 4 ) which span the visible and NIR regions.…”
Section: Resultsmentioning
confidence: 99%
“…Here 25% of the OHions of the M(OH) 2 layers are replaced by NO -3 ions which are coordinated directly to the metal matrix. 7,8 Hydroxy double salts are hydroxysalts of the above-mentioned types containing two different metal ions. A number of hydroxy double salts of the zinc hydroxynitrate type have been studied in the past.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Sm(OH) 2 NO 3 seems to be correctly described in the acentric space group. Besides, one overcomes the problem of half-occupied sites as discussed in Louer et al (1989).…”
Section: Discussionmentioning
confidence: 99%
“…These chains are additionally edge-linked, thus forming sheets. [For further details see Lundberg and Skarnulis (1976), Mullica et al (1986), and Louer et al (1989).] The sheets are interconnected by hydrogen bonding only, causing the pronounced preferred orientation due to texture observed in the powder pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation